Precise micromotion compensation of a tilted ion chain - Hogle, Craig W.; Burch, Ashlyn D.; Sterk, Jonathan D.; Chow, Matthew N. H.; Ivory, Megan; Lobser, Daniel S.; Maunz, Peter; Van Der Wall, Jay; Yale, Christopher G.; Clark, Susan M.; Stick, Daniel; Revelle, Melissa C. (Frontiers in Quantum Science and Technology, 2024)
Excess micromotion can be a substantial source of errors in trapped-ion based quantum processors and clocks due to the sensitivity of the internal states of the ion to external fields and motion. This problem can fixed by compensating background electric fields in order to position ions at the RF node and minimize their driven micromotion. Here we describe techniques for compensating ion chains in scalable surface ion traps. These traps are capable of cancelling stray electric fields with fine spatial resolution in order to compensate multiple closely spaced ions due to their large number of relatively small control electrodes. We demonstrate a technique that compensates an ion chain to better than 5 V/m and within 0.1 degrees of chain rotation.